Concordance of antioxidant and anti-Inflammatory activity in Xylocarpus granatum (Koen): Antiox. & Anti-Inflam. Activity of X. granatum - Islam, Md Emdadul; Rahman, SM Mahbubur; Sohrab, Md Hossain; Biswas, Rana; Ullah, Mohammad Shaef; Islam, Kazi Didarul (Journal of the Bangladesh Agricultural University, 2019)
Xylocarpus granatum, a common mangrove plant is traditionally used for the treatment of diarrhoea, cholera, fever, dyslipidemia, inflammation, etc. The present study was carried out to evaluate the antioxidant and anti-inflammatory potential of the ethanolic extract of X. Granatum by various in vitro methods such as 1,1-diphenyl-2-picryl-hydrazil (DPPH) free radical scavenging assay, reducing power assay, ferric reducing antioxidant power (FRAP) and β-carotene bleaching inhibition assay. Total phenolic and flavonoid content were determined. Anti-inflammatory activity was evaluated by in vitro human RBC membrane stabilizing assay and in vivo mice paw edema test. Ethanolic leaf extract (S2) of X. granatum showed significant scavenging effect on DPPH scavenging with a value of IC50 165.95µg/ml. In addition, it showed significant reducing potential with a value of 59.04 mM of ferrous equivalent per ml in FRAP assay and in reducing power assay the EC50 value was determined as 241.61μg/ml . The ethanolic leaf extracts exhibited 72.3% β-carotene bleaching inhibition. The total phenolic and flavonoid content of the extract were 66μg/ml gallic acid equivalent and 47.66μg/ml quercetin equivalent per gram of dry extract, respectively. The extract also exhibited 52.63% and 51.05% protection of RBC membrane in hypotonicity and heat induced lysis inhibition, respectively. Significant reduction of mice paw edema (36.34% in 20 μg/kg bw concentration) was observed in the extract. The results revealed that the leaf extract of X. granatum possesses strong antioxidant and anti-inflammatory potential. <!--StartFragment --> J Bangladesh Agril Univ 17(4): 466–475, 2019